In-Vitro evaluation of antimicrobial activity of Allium sativum and Zingiber Officinale against multi-drug resistant clinical pathogens. - Rafique , Ambreen; Baig, Nida; Mehboob, Aneela; Zahid , Ramsha; Irfan , Amna (International Journal of Endorsing Health Science Research, 2022)
Background: Clinically significant microbes have evolved over time and developed such mechanisms to protect themselves from synthetic drugs. This study aims to determine the antimicrobial activity of culinary condiments against multi-drug resistant clinical pathogens. Methodology: The antimicrobial activity of Allium sativum (garlic) and Zingiber Officinale (ginger) was assessed against clinical pathogens such as E. coli, P. aeruginosa, and S. aureus. with the aid of wet experiments, namely disc diffusion method, and well agar technique. Results: It was observed that both A. sativum and Z. officinale in their neat form were very effective against tested pathogens ranges from 16 ± 0.623 mm to 36 ± 0.816 mm and 19 ± 0.707 to 20 ± 1.414 mm respectively as compared to the other concentrations with peptone water and distal water. However, extract A. sativum showed more antibacterial strength than Z. officinale. Conclusion: Natural antimicrobial agents obtained from herbs and spices could be effective alternatives to treat various infections with minimum to no side effects.